Effect of manifold and port injection of hydrogen and exhaust gas recirculation (EGR) in dairy scum biodiesel - low energy content gas-fueled CI engine operated on dual fuel mode. (1st February 2022) - Yaliwal, V.S.; Banapurmath, N.R.; Soudagar, Manzoore Elahi M.; Afzal, Asif; Ahmadi, P.
Abstract: In this current work, exhaustive research work is conducted in three phases, in the initial phase, WFO was used for producing WFO treated biomass and in the second phase, influence of PFIP and PFIT has been examined. Further in the successive phase, effect of hydrogen HMI, HPI and EGR on the combustion and emission characteristics of CRDI diesel engine operated on dual-fuel mode using DiSOME and PG combination is evaluated. In the current study, in a CRDI engine, PFIT was employed ranging from 0 to 15°CA bTDC and changed in steps of 5 and PFIP was used from 600 to 1000 bar and varied in successive steps of 200 bar. Further flow rate of hydrogen was kept 8 L/min constant and HMIT was employed in the range from TDC to 15°aTDC and changed in stages of 5. Correspondingly, HID was varied from 30 to 90°CA with 30°CA dwell and EGR was used in the range from 0 to 15% by vol. and varied in steps of 5. Outcome of the work showed that, DiSOME-PG operation with 10°bTDC PFIT, 800 bar PFIP, 10°aTDC of HMI, 60°CAHID and 5% EGR rate showed lower BTE by 5.8% and increased smoke levels by 10.8%, HC by 8.6%, CO by 6.5% and marginally decreased NOx by 6.4% was observed in comparison to the same fuel blend with zero EGR at 80% load. Further, marginally amplifiedID and CD with loweredCP and HRR has been noticed. Study revealed thatH2 addition to low calorific value gas (PG), method of pilot fuel addition and EGR is affected dual fuel engine performance, but provided drastic reductions in smoke and NOx emissions. Highlights: Examinations on a 4 stroke 1 cylinder water cooled diesel engine on DF mode. Influence on DF engine of PFIP and PFIT performance. Effect of HMI, HPI, EGR on combustion & emission attributes of CRDI diesel engine. EGR supply significantly affect the dual fuel engine combustion and emission levels. BTE reduced by 5.8%, NOx by 6.4%, and increased smoke levels by 10.8%, HC by 8.6%.